Environmental flows in water resources policies, plans, and projects : findings and recommendations - Hirji, Rafik (Environment and development (Washington, D.C.), 2009)
This book advances the understanding and integration in operational terms of environmental flows (water allocation) into integrated water resources management (IWRM). Based on an in-depth analysis of 17 global water policy, plan, and project case studies, it addresses the highly contested complexities of environmentally responsible water resources development, broadens the global perspectives on?equitable sharing? and?sustainable use? of water resources, and expands the definitions of?benefits sharing? in high-risk water resources development. The book fills a major gap in knowledge on IWRM.